2018
DOI: 10.1038/s41561-018-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for a substantial sea-level fluctuation within the Last Interglacial

Abstract: This is a repository copy of Lack of evidence for a substantial sea-level fluctuation within the Last Interglacial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 107 publications
(61 reference statements)
4
43
0
Order By: Relevance
“…Hearty et al, 2007;Blanchon et al, 2009;Kopp et al, 2013;O'Leary et al, 2013;Murray-Wallace and Woodroffe, 2014), although we note that other studies have disputed this (e.g. Long et al, 2015;Barlow et al, 2018). Most of our selected ESL and RSL curves do not reflect interglacial SL variability, indicating that short-wavelength peaks may be underrepresented in most SL curves and limit the number of matched terraces for the Xylokastro sequence.…”
Section: Approach Limitationsmentioning
confidence: 76%
“…Hearty et al, 2007;Blanchon et al, 2009;Kopp et al, 2013;O'Leary et al, 2013;Murray-Wallace and Woodroffe, 2014), although we note that other studies have disputed this (e.g. Long et al, 2015;Barlow et al, 2018). Most of our selected ESL and RSL curves do not reflect interglacial SL variability, indicating that short-wavelength peaks may be underrepresented in most SL curves and limit the number of matched terraces for the Xylokastro sequence.…”
Section: Approach Limitationsmentioning
confidence: 76%
“…To confidently confirm these rapid sea-level changes at a global scale, more evidence needs to be amassed from geographically diverse sites with robust chronologies. Some recent studies have argued that a sea-level fall of >4 m, as indicated by Kopp et al (2009), is not plausible given constraints from phreatic overgrowths in Mallorca caves (Polyak et al 2018) and other lines of observational and modeling evidence (Barlow et al 2018). However, these studies do not preclude the possibility of smaller, meter-scale sea-level fluctuation(s) in the low latitude reef sites during the LIG (Fig.…”
Section: Evolution Of the Sea-level Highstandmentioning
confidence: 93%
“…The LIG sea-level highstand that persisted from ~129 to 116 thousand years (kyr) ago has long been acknowledged to be higher than present sea level, though the magnitude of peak sea level and the stability of sea level during the highstand are still actively debated (Dutton et al 2015a;Austermann et al 2017;Barlow et al 2018). While there are important differences between modern, anthropogenically-driven global warming and the orbitally driven warmth of the LIG, there are several relevant and valuable observations to be made.…”
mentioning
confidence: 99%
“…The LIG sea-level highstand that persisted from ~129 to 116 thousand years (kyr) ago has long been acknowledged to be higher than present sea level, though the magnitude of peak sea level and the stability of sea level during the highstand are still actively debated (Dutton et al 2015a;; Barlow et al 2018). While there are important differences between modern, anthropogenically-driven global warming and the orbitally driven warmth of the LIG, there are several relevant and valuable observations to be made.…”
Section: Summary and Future Workmentioning
confidence: 99%